2014
DOI: 10.17221/266/2013-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

In vitro elimination of Black raspberry necrosis virus from black raspberry (Rubus occidentalis) - Short Communication

Abstract: Cheong E.J., Jeon A.R., Kang J.W., Mock R., Kinard G., Li R., 2014. In vitro elimination of Black raspberry necrosis virus from black raspberry (Rubus occidentalis) -Short Communication. Hort. Sci., 41: 95-99. Black raspberry necrosis virus (BRNV) is one of the most important viral pathogens ofRubus spp. In this study, a procedure combining in vitro culture and heat therapy on axillary buds of Rubus occidentalis was developed to eliminate BRNV from infected plants. Axillary buds were grown aseptically at 4-h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Working on combining thermotherapy with shoot tip culture for virus eradication from pear, Tan et al [ 63 ] found that survival levels, shoot length and proliferation efficiency of in vitro shoots decreased, while virus-free frequencies of ACLSV and ASPV increased, as thermotherapy durations increased from 10 to 50 days. Negative effects of prolonged thermotherapy durations on in vitro shoots and shoot tips excised from the treated shoots were frequently found in woody plants such as apricot [ 64 ], peach [ 64 ], cherry [ 64 ], pear [ 65 , 66 ], plum [ 62 ] and black raspberry [ 67 ], and herbaceous species such as horseradish [ 58 ], chrysanthemum [ 33 ], begonia [ 63 ] and potato [ 64 ]. Increased virus eradication frequencies by increasing thermotherapy durations were also frequently reported in various virus-host combinations.…”
Section: Key Factors Affecting Success Of Virus Eradicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Working on combining thermotherapy with shoot tip culture for virus eradication from pear, Tan et al [ 63 ] found that survival levels, shoot length and proliferation efficiency of in vitro shoots decreased, while virus-free frequencies of ACLSV and ASPV increased, as thermotherapy durations increased from 10 to 50 days. Negative effects of prolonged thermotherapy durations on in vitro shoots and shoot tips excised from the treated shoots were frequently found in woody plants such as apricot [ 64 ], peach [ 64 ], cherry [ 64 ], pear [ 65 , 66 ], plum [ 62 ] and black raspberry [ 67 ], and herbaceous species such as horseradish [ 58 ], chrysanthemum [ 33 ], begonia [ 63 ] and potato [ 64 ]. Increased virus eradication frequencies by increasing thermotherapy durations were also frequently reported in various virus-host combinations.…”
Section: Key Factors Affecting Success Of Virus Eradicationmentioning
confidence: 99%
“…SA treatments decreased catalase activity and increased hydrogen peroxide (H 2 O 2 ) levels of the in vitro potato shoots, thus enhancing their tolerance to thermotherapy [ 65 , 66 ]. SA induced plant defense to virus infection and was beneficial for virus eradication [ 67 ]. Therefore, SA had double positive effects in thermotherapy for virus eradication: enhancing plant tolerance to thermotherapy and increasing virus eradication frequency.…”
Section: Key Factors Affecting Success Of Virus Eradicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation coefficient among plantlet survival after heat treatment (%), meristems survival (%) in tissue culture at 30 days after excision, meri-clone regeneration after 45 days (%) and virus free meri-clones (%). meristem regeneration efficiencies implying differences in cultivars for meristem culture and meri-clone regeneration (Cheong et al, 2014;Danci et al, 2012;Biniam and Tadesse, 2008). Virus-free meri-clones were obtained in both heat treated and controls plantlets, however, the virus-free success rate was higher in the former than the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used procedures for viruses and viroids are meristem culture, somatic embryogenesis combined or not with thermotherapy, and chemotherapy (Panattoni et al, 2013;Parštein et al, 2013;Cheong et al, 2014). For instance, in grape, meristem culture has been used for the production of viroid-free grapevines (DuranVila et al, 1988) and also to clean plants infected with GFLV, GLRaV-1, and GLRaV-3 (Youssef et al, 2009;Shatnawi et al, 2011).…”
Section: Embryogenesis Protocol For Sanitation Of Grapementioning
confidence: 99%